Exploring a generalized nonlinear multi-span bridge system subject to multi-support excitation using a Bouc-Wen hysteretic model - Meibodi, A.A; Alexander, Nicholas A. (Soil dynamics and earthquake engineering (1984), 2020)
This paper presents a generalized reduced-order nonlinear model subjected to multi-support seismic excitation. The hysteretic, nonlinear, relationship of piers is phenomenologically captured by a calibrated Bouc-Wen model. This generalized reduced-order model is benchmarked against legacy physical experimental tests performed at the University of Bristol. A deterministic approach using real spatiotemporal ground motions recorded at the SMART-1 array, Taiwan, is employed as an alternative to a stochastic methodology used in current provision codes. This is so that the influence of nonlinearity and ground motion aleatory and epistemic effects are fully captured. Incremental Dynamic Analysis (IDA) is then performed to identify the performance levels at which this system transitions from elastic to inelastic behaviour. A parametric study is then performed to explore the effect of the spatial variability of the ground motion while bridge alignment, valley profile and ground motion intensity are modified. Results indicate that bridges over shallow valleys with a central rise are prone to significant analysis errors if multi-support excitation is not employed. •A generalized reduced-order nonlinear model of a multi-span bridge under asynchronous excitation is proposed.•Hysteretic behavior of piers is facilitated by a generalized Bouc-Wen model.•The effect of certain valley profiles on bridge responses to the spatial variability of ground motions is significant.